Applicability of the Dea Method on the Transport Undertakings in Selected Regions - Kampf, Rudolf; Cejka, Jiri; Telecky, Martin (Communications - Scientific letters of the University of Zilina, 2016)
With respect to achieving the economic goals within ordering of the suitable public transport system it is currently necessary that the economic indicators which contribute to the amount of a provable loss be evaluated rationally. The authors, therefore, will use the DEA method to efficiently assess the economic situation of the specific transport company to find out whether its business is economically attractive. At the same time, the involved companies will be compared with respect to their economically attractive behaviour. The article is based on the public domain information – economic indicators which the undertakings are obliged to publish by law. Despite this fact, it can be concluded that the source data are suitable for the analysis of economic health of a particular transport company.